Safety and 30-day outcomes of tracheostomy for COVID-19: a prospective observational cohort study. (December 2020) - ,; Breik, Omar; Nankivell, Paul; Sharma, Neil; Bangash, Mansoor N.; Dawson, Camilla; Idle, Matthew; Isherwood, Peter; Jennings, Christopher; Keene, Damian; Manji, Mav; Martin, Tim; et al.
Abstract: Background: The role of tracheostomy in coronavirus disease 2019 (COVID-19) is unclear, with several consensus guidelines advising against this practice. We developed both a dedicated airway team and coordinated education programme to facilitate ward management of tracheostomised COVID-19 patients. Here, we report outcomes in the first 100 COVID-19 patients who underwent tracheostomy at our institution. Methods: This was a prospective observational cohort study of patients confirmed to have COVID-19 who required mechanical ventilation at Queen Elizabeth Hospital, Birmingham, UK. The primary outcome measure was 30-day survival, accounting for severe organ dysfunction (Acute Physiology and Chronic Health [APACHE]-II score>17). Secondary outcomes included duration of ventilation, ICU stay, and healthcare workers directly involved in tracheostomy care acquiring COVID-19. Results: A total of 164 patients with COVID-19 were admitted to the ICU between March 9, 2020 and April 21, 2020. A total of 100 patients (mean [standard deviation] age: 55 [12] yr; 29% female) underwent tracheostomy; 64 (age: 57 [14] yr; 25% female) did not undergo tracheostomy. Despite similar APACHE-II scores, 30-day survival was higher in 85/100 (85%) patients after tracheostomy, compared with 27/64 (42%) non-tracheostomised patients relative risk: 3.9 (95% confidence intervals [CI]: 2.3–6.4); P <0.0001. In patients with APACHE-II scores ≥17, 68/100 (68%) tracheotomised patients survived, compared with 12/64 (19%) non-tracheotomised patients ( P <0.001). Tracheostomy within 14 days of intubation was associated with shorter duration of ventilation (mean difference: 6.0 days [95% CI: 3.1–9.0]; P <0.0001) and ICU stay (mean difference: 6.7 days [95% CI: 3.7–9.6]; P <0.0001). No healthcare workers developed COVID-19. Conclusion: Independent of the severity of critical illness from COVID-19, 30-day survival was higher and ICU stay shorter in patients receiving tracheostomy. Early tracheostomy appears to be safe in COVID-19.